SPONTANEOUS BACTERIAL PERITONITIS IN ASYMPTOMATIC CIRRHOTIC PATIENTS WITH ASCITES IN A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY - Aziz, Asif; Ashraf, Sarwat; Talpur, Mir Tahir Hussain; Aamer, Nasrullah; Solangi, Sagheer Ahmed; Shabir, Khalil Ullah; Ahmed, Moiz; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of spontaneous bacterial peritonitis in asymptomatic cirrhotic patients with ascites. Study Design: Cross-sectional study. Place and Duration of Study: Medical outpatient department, Medical unit III, Ward-7, JPMC, Karachi, from Feb 2018 to Aug 2018. Methodology: All patients between the age of 18 to 60 years and presenting with confirmed ascites due to liver cirrhosis were included. Those with ascites due to other causes were excluded from the study. After obtaining consent, diagnostic ascitic paracentesis was done and sent to the laboratory for evaluation. Results: A total of 130 patients were enrolled in the study. The mean age of ascites patients was 46.94 ± 7.67 years. There were 73 (56.2%) male while 57 (43.8%) were female. Spontaneous bacterial peritonitis was detected among 38 (29.2%) patients. Among these, 15 patients (11.5%) had positive culture of spontaneous bacterial peritonitis and detected organisms like E.coli (5.4%), Klebsiella (3.1%), Pneumococcus (2.3%) & Streptococcus viridians (0.8%). Frequency of spontaneous bacterial peritonitis increased with increasing age. Male gender was more affected of spontaneous bacterial peritonitis. Lower the weight increasing duration of ascites were associated with higher incidence of spontaneous bacterial peritonitis (p-value = 0.001 and 0.311 respectively). Conclusion: Spontaneous bacterial peritonitis was detected among one-third of the patients suffering from cirrhosis, making it a grave complication that requires prompt treatment.